Media Reality Construction of Refugees Rohingya - Rasyid, Muhammad Ahlam; Abdurrahman, Muhammad Sufyan (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
In the news published by Republika.co.id, Kompas.com, and Kumparan.com, it was reported that Rohingya refugees who came to Aceh to get help and protection surprised the people of Aceh. Of course, the arrival of Rohingya refugees in Aceh raises various opinions from the people of Aceh itself. This research focuses on analysing the construction of reality from the news media using Robert N. Entman's framing analysis. This research aims to find out how Republika.co.id, Kompas.com, Kumparan.com media frame the reality related to the news of Rohingya refugees in Aceh. The methodology used for this research is by conducting a qualitative approach with Robert N. Entman's framing analysis model, by looking at the selection of issues and emphasis on aspects with Entman's four models, namely problem identification, diagnosis of the cause of the problem, moral judgement, and problem solving recommendations. The results show that Republika.co.id sees more through the Islamic view of the presence of Rohingya refugees based on religious principles. Kompas.com sees based on the view of Nationalism towards the condition of the Acehnese people from the arrival of Rohingya refugees in Aceh. Kumparan.com sees the issue as news that can increase the amount of income and readers, so each media has its own views on the issue. Researchers also present the ideology of each media so that it can influence the news text produced. This analysis focuses on the role of the media in presenting news in controversial issues so that it can affect news value